Effect of Metabolizable Energy and Crumble Quality of the Diet on Growth Performance of Broilers - Nelsa M. Beckman; Khairy I Jenkins; Allison K. Blomme; Haley K. Otott; Kara M. Dunmire; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2022)
In order to optimize the growth performance of broilers, diets are formulated to a recommended ME concentration. In addition, broilers (chicks) are often fed diets in the form of crumbles in early production to improve growth performance. Thus, the objective of this study was to determine the effect of ME concentration in diets and if removal of crumble fines influenced the growth performance response of broilers. At hatch, a total of 300 one-day-old male broilers (Cobb 500, initial BW 0.093 lb) were used in an 18-day study. Broilers were housed in 3 Petersime batteries with ad libitum access to feed and water. Treatments were randomly assigned to 60 cages balanced by location, resulting in 10 cages per treatment with 5 broilers per cage. Treatments were arranged in a 2 × 3 factorial of ME content (1,376 and 1,346 ME, kcal/lb) and crumbled diets with or without fines (removed particles<1,532 µm or<864 µm). Crumble treatments were fed with no sifting (NS) or sifted using either a screen with 0.06-in. openings (removed particles<1,532 µm) or a screen with 0.03-in. openings (removed particles<864 µm). Data were analyzed as a completely randomized design using the GLIMMIX procedure of SAS (v. 9.4, SAS Institute, Inc., Cary, NC). There was no evidence of an interaction between crumble fines removal and ME or main effect of ME. Body weight gain (BWG) and total feed intake (TFI) increased (P<0.05) when broilers were fed crumbles sifted with a 0.06-in. screen compared to NS and crumbles sifted with a 0.03-in. screen. Broiler feed conversion ratio (FCR) improved (P<0.001) when broilers were fed crumbles sifted with a 0.06-in. screen compared to those fed NS and sifted with a 0.03-in. screen. In conclusion, broilers fed crumbles with particles<1,532 µm removed had an improved FCR and an increased BWG and TFI regardless of the ME content of the diet. Increasing ME from 1,346 to 1,376 kcal/lb did not influence growth performance of broilers from d 0 to 18 d of age.
Keywords: crumble; metabolizable energy; broiler; growth performance